M-Type SrFe12O19 Ferrite: An Efficient Catalyst for the Synthesis of Amino Alcohols under Solvent-Free Conditions - Mouhsine Laayati; Ali Hasnaoui; Nayad Abdallah; Saadia Oubaassine; Lahcen Fkhar; Omar Mounkachi; Soufiane El Houssame; Mustapha Ait Ali; Larbi El Firdoussi (Journal of Chemistry)
Magnetically separable strontium hexaferrite SrFe12O19 was prepared using the chemical coprecipitation method, and the nanostructured material was characterized by X-ray diffraction, scanning electron microscopy (SEM), energy-dispersive spectrometry (EDS), and BET analysis. The SEM images showed the homogeneity of the chemical composition of SrFe12O19 and uniform distribution of size and morphology. The pore size of the nanomaterial and its specific area were determined by BET measurements. Strontium hexaferrite SrFe12O19 exhibited a strong magnetic field, which is highly suitable in the heterogeneous catalysis as it can be efficiently separated from the reaction. The magnetic nanocatalyst showed high activity and environmentally benign heterogeneous catalysts for the epoxide ring-opening with amines affording β-amino alcohols under solvent-free conditions. When unsymmetrical epoxides were treated in the presence of aromatics amines, the regioselectivity was influenced by the electronic and steric factors. Total regioselectivity was observed for the reactions performed with aliphatic amines. The magnetically SrFe12O19 nanocatalyst showed excellent recyclability with continuously good catalytic activities after four cycles.